Chinese business English undergraduates’ speaking proficiency: a developed-module effect - Hu, Ke; AlSaqqaf, Asmaa (International Journal of Evaluation and Research in Education (IJERE), 2024)
The rapid growth of English in the world has resulted in its vital role in diverse domains. However, the outcomes of learners' speaking skills remain controversial. The objective of the study was to investigate the effect of the developed teaching speaking module on the speaking proficiency of 96 Chinese English as a foreign language (EFL) business English undergraduates at the target applied university in China. This module integrates content-based instruction (CBI) and a three-stage skill development approach, namely awareness-raising, appropriation, and autonomy (3As approach). A quantitative study with a pretest and posttest quasi-experiment design was carried out at an applied university within an interventional period of 10 weeks, employing pretests and posttests as data collection tools. The quantitative data were analyzed using the SPSS 29 version suggesting that this teaching-speaking module yields significantly improved speaking proficiency among Chinese EFL undergraduates in business English than the traditional classroom has done. These findings shed a favorable light on the development of curriculum and instruction for teaching English for specific purposes (ESP) and the education of English majors in China.